Pembentukan Akhlak Berbasis Pembiasaan Dan Keteladanan (Studi Kasus Di MAN 2 Kuningan Jawa Barat) - Siti Nurjanah (Oasis : Jurnal Ilmiah Kajian Islam, 2020)
The purpose of this study was to determine the moral formation of learners based on habituation and exemplary, and to determine the success of the formation of habitual morals and exemplary in Madrasa Aliya Negeri 2 Kuningan, West Java. The author uses a qualitative method with a phenomenological approach, so in collecting data, the author uses observation techniques, in-depth interviews, documentation and using the data technique child can data model Miles and Huberman. Habit based and exemplary moral formation in Madrasa Aliya Negeri 2 Kuningan West Java was carried out with various activities, namely: Habit of dhuhur prayer in congregation, habituation of Infaq every Friday morning, habituation of Asr prayer in congregation, habituation of tadarus al-Qur'an, habituation of tahfizd together every Monday the flag ceremony is over, habituation of yasinan and khitobah (lectures) every Friday morning, habituation in dress. The exemplary moral-based formation is carried out with various activities, namely: discipline, honesty, responsibility, humility, emotional control, the ability of the teachers to control emotions differently, some are good so that they think first before acting, polite, average the average teacher shows a polite attitude, both in speaking and behaving, exemplary by civilizing the S5, exemplary welcoming students in front of the gate, so that citizens of Madrasa Aliya Negeri 2 Kuningan can improve their religion (religious), change attitudes (akhlakul karimah), love to read and improve concern for the environmentTujuan dari penelitian ini adalah untuk mengetahui pembentukan akhlak peserta didik berbasis pembiasaan dan keteladanan, serta untuk mengetahui keberhasilan dari pembentukan akhlak pembiasaan dan keteladanan di Madrasah Aliyah Negeri (MAN) 2 Kuningan Jawa Barat. Penulis menggunakan metode kualitatif dengan pendekatan fenomenologi, maka dalam pengumpulan data, penulis menggunakan teknik observasi, wawancara mendalam, dokumentasi dan mengunakan teknik anak bisa data model Miles dan Huberman. Pembentukan akhlak berbasis pembiasaan dan keteladanan di MAN 2 Kuningan Jawa Barat dilakukan dengan berbagai kegiatan, yaitu:Pembiasaan shalat dhuhur berjama’ah, pembiasaan Infaq setiap jum’at pagi, pembiasaan Shalat Ashar berjamaah, pembiasaan tadarus al-Qur’an, pembiasaan tahfizd bersama setiap senin selesai upacara bendera, pembiasaan yasinan dan khitobah (ceramah) setiap jum’at pagi, pembiasaan dalam berpakaian. Adapun pembentukan akhlak berbasis keteladanan dilakukan dengan berbagai kegiatan, yaitu: kedisiplinan, kejujuran, tanggung jawab, rendah hati, pengendalian emosi, kemampuan guru-guru mengendalikan emosi berbeda-beda, ada yang baik sehingga berpikir terlebih dahulu sebelum bertindak, sopan santun, rata-rata guru menunjukkan sikap yang sopan, baik dalam berbicara maupun bertingkah laku, keteladanan dengan membudayakan S5, keteladanan menyambut peserta didik di depan gerbang, sehingga warga MAN 2 Kuningan dapat meningkatkan keimanan (religius), merubah sikap (akhlakul karimah), gemar membaca dan meningkatkan kepedulian terhadap lingkungan.